Respostas

2014-06-21T16:40:24-03:00
x² - 2y = 0
4x - y = 8

- y = 8 - 4x
y = - 8 + 4x

x² - 2 (- 8 + 4x) = 0
x² + 16 - 8x = 0

a = 1              b = - 8             c = 16

Δ = b² - 4 * a * c
Δ = (- 8)² - 4 * 1 * 16
Δ = 64 - 64
Δ = 0

Obs: Quando o Δ (Delta) for 0 (zero) só há uma raiz.

x = - b ± √Δ
     ________
       2 * a
x = - (- 8) ± √0
      __________
            2 * 1
x = 8 ± 0
     ______
         2
x = 8 
÷ 2
x = 4

y = - 8 + 4x
y = - 8 + 4 * 4
y = - 8 + 16
y = 8

Resposta: 
x = 4; y = 8